ISLAMOPHOBIA: LITERATURE REVIEW OF ITS DEFINITIONS AND EARLY TWENTY FIRST CENTURYAPPROXIMATIONS - Riaz, Humaira; Qadir, Samina A. (International Journal of Psychosocial Rehabilitation, 2020)
Review of the previous studies finds a high magnitude in the contemporary research scenario. It proves a significant tool to inform scholars how to create a decipherable synthesis of the best resources available in literature to engender guidelines for starting point. Qualitative in nature, this paper critically evaluates the selected documented literature on Islamophobia. It explores the development of Islamophobia over a period of time and discusses its definitions to argue that bias and prejudice based on irrational fear of Islam and Muslims are helpful in understanding the spread of Islamophobia in Western and American societies. It also investigates how contemporary global situation develops a new stance on intersection of racism and religion. The paper concludes that complexities of the existence of Islamophobia in Western and American society make it difficult to explore its presence. A closer and clearer identification possibly will lead to effective ways of reducing Islamophobia.